Message in a bottle: Generation Y and wine purchase occasions’ perceived risks and information sources - Brochado, A.; Rodrigues, H.; Mendes , S. (Strategic management in the wine tourism industry: Competitive strategies, wine tourism behaviour and new strategic tools, 2024)
This study focused on Portuguese Generation Y wine consumers’ purchase behaviour for different occasions. The latter were defined by two variables: where (i.e. home, gift-giving and restaurant) and who (i.e. myself, friends, family, partner and colleagues). A sample of 477 Portuguese millennials provided the primary data. The research included cross-tabulating product attributes, perceived risks and information sources with wine consumption occasions. The results show that occasion-based segmentation is an effective way to investigate Portuguese Generation Yers’ wine consumption. The findings also reveal more associations between wine attributes, wine consumption risks and information sources for the occasions defined by the variable where as compared with those delineated by who. Overall, occasion-related tactics are always crucial when creating wine industry strategies. This book chapter provides information useful to wine business professionals and academics.